Fase-Fase Pendidikan Anak dalam Konteks Hadits - Al Birruni Siregar; Chusnul Chotimah (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2025)
The success of a child's education not only depends on his intellectual intelligence, but also on the formation of his character, attitudes and behavior. One of the main sources of guidance for Muslims in forming character is the hadith. This research aims to explore in depth the phases of children's education in the context of the An-Nabawi hadith. This research includes qualitative and library research. Based on this study, the relationship between parents and children, which actually starts from the pre-natal period, has required parental attention since that period. Apart from that, there are three general phases divided by KH. Ahmad Mustain Syafi'i, namely the initial stage 0-7 years, the second stage 7-14 years, and the third stage 14-21 years. It is hoped that this study can provide a more comprehensive and in-depth view of the contribution of hadith in guiding and directing children's education.